Engineering Skills: Employer Satisfaction Among Malaysian Graduate Engineer - Saleh, Hasan; Lamsali, Hendrik (Penerbit Universiti Teknikal Malaysia Melaka, 2019)
The purpose of this study is to investigate the employers’ satisfaction in regard to the skill of engineering graduates. This study use 195 survey questionnaire distributed to the manufacturing senior manager at Melaka, Negeri Sembilan and Pulau Pinang only. Statistical Package for Social Science (SPSS) software version 22.0 have been used to extract the data needed from the survey. From this study, the finding indicates that employer are satisfy with the skill equipped to the engineering graduates and show that fundamental general skill (FGS)(B=0.330, p=0.000) and engineering skills (EgS)(B-0.286, p=0.000) are the most important and essential to employer satisfaction. The results from this study offer an important practical implication for engineering graduates to be successful in employability. Proper skills are needed to get employer satisfaction for employability with the necessary skill equipped to the engineering graduates. It is hope with this data it can be an essential reference for engineering graduates to prepare themselves to enter the working environment in today’s challenging economic situation